DNA methylation profiling to predict recurrence risk in meningioma: development and validation of a nomogram to optimize clinical management - Nassiri, Farshad; Herold-Mende, Christel; Sahm, Felix; Deimling, Andreas von (Neuro-Oncology, 2019)
Background. Variability in standard-of-care classifications precludes accurate predictions of early tumor recurrence for individual patients with meningioma, limiting the appropriate selection of patients who would benefit from adjuvant radiotherapy to delay recurrence. We aimed to develop an individualized prediction model of early recurrence risk combining clinical and molecular factors in meningioma.